Solar flare catalogue from 3 years of Chandrayaan-2 XSM observations - Valluvan, Aravind Bharathi; Goyal, Ashwin; Jain, Devansh; Samantaray, Abhinna Sundar; Sarwade, Abhilash; Sankarasubramanian, Kasiviswanathan (Solar physics, 2024)
We present a catalogue of 6266 solar flares detected by the Solar X-ray Monitor onboard the Chandrayaan-2 lunar orbiter between 1.55 and 12.4 keV (1 and 8 Å) from 2019 September 12 to 2022 November 4, including 1469 type A flares. The catalogue represents the first large sample, including both type A, hot thermal flares, and type B, impulsive flares, with a sub-A-class sensitive instrument. We also detect 213 sub-A and 1330 A-class flares. Individual flares are fitted with an exponentially-modified Gaussian function and multi-flare groups are decomposed into individual flares. We validate our findings with flare catalogues made using visual inspection as well as automatic pipelines on Geostationary Operational Environmental Satellite and Solar Dynamics Observatory data. We find a clear bimodality in the ratio of the width to decay time between type A and B flares. We infer a power-law index of αF = 1.92 ± 0.09 for the background-subtracted peak flux distribution of XSM flares, which is consistent with the value $\sim 2$reported in the literature. We also infere αF = 1.90 ± 0.09 for type B, and αF = 1.94 ± 0.08 for type A flares, which has previously not been reported in the literature. These comparable values hint at a similarity in their generative processes.